2015
DOI: 10.1016/j.bbamem.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C affects the internalization and recycling of organic anion transporting polypeptide 1B1

Abstract: Organic anion-transporting polypeptides are members of the solute carrier (SLC) family and key determinants for the transmembrane transport of a wide variety of compounds. OATP1B1 is predominantly expressed at the basolateral membrane of human hepatocytes and play an important role in drug clearance from the body. It has been demonstrated to be responsible for the hepatic uptake of various drugs. Computer-based hydropathy analysis predicted several putative phosphorylation sites at the amino and carboxyl termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…Previous studies have demonstrated that PKC activation can rapidly modulate drug and bile acid transporter location and activity in hepatocytes, by notably promoting their retrieval from sinusoidal or canalicular membranes [49][50][51] or modulating their phosphorylation status [16]. The present study demonstrates that in vitro PKC activation caused by PMA can also result in marked changes in expression of main hepatic drug transporters.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Previous studies have demonstrated that PKC activation can rapidly modulate drug and bile acid transporter location and activity in hepatocytes, by notably promoting their retrieval from sinusoidal or canalicular membranes [49][50][51] or modulating their phosphorylation status [16]. The present study demonstrates that in vitro PKC activation caused by PMA can also result in marked changes in expression of main hepatic drug transporters.…”
Section: Discussionsupporting
confidence: 49%
“…Taken together, these data fully establish PKCs as important regulators of Hepatic transporters whose expression is targeted by the PKC activator PMA include major and relevant SLC transporters, such as OATP1B1, OATP2B1 and OCT1, involved in sinusoidal uptake of various marketed drugs such as statins and metformin [2]. These SLC transporters were down-regulated at the mRNA level in both HepaRG cells and primary human hepatocytes exposed to PMA; some of them, i.e., OATP1B1 and OATP2B1, whose membrane location is already known to be rapidly modulated by PKCs [50,52], were concomitantly decreased at the protein level and also targeted by the PKC activator agent ingenol mebutate. Importantly, OATP and OCT1 activity were reduced in parallel, thus indicating that PMA-mediated repression of transporter expression results into functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The PKC activator agent PMA has thus been shown to stimulate internalization of OATP transporters such as OATP1A2, OATP1B1 and OATP2B1 in cultured cells [66,67,68]. As an example, cell surface expression of OATP2B1 at the sinusoidal pole of human highly-differentiated hepatoma HepaRG cells was markedly decreased in response to a short 1-h treatment with 100 nM of PMA (Figure 2a).…”
Section: Pkcs-dependent Regulation Of Drug Transporter Localizationmentioning
confidence: 99%
“…PKC-triggered OATP1A2 internalization in COS-7 cells transfected with OATP1A2 was blocked by the cPKC inhibitor Gö6976 and was dependent on clathrin-dependent endocytosis, but not on the caveolin-dependent pathway [66]. Similarly, OATP2B1 internalization caused by PMA was related to clathrin-mediated endocytosis, followed by lysosomal degradation in OATP2B1-transfected MDCKII cells [68], whereas internalized OATP1B1 co-localized with early and recycling endosomal markers in OATP1B1-transfected HEK293 cells [67]. Activation of PKCs by PMA also results in altered trafficking of the ENT1 nucleoside transporter, with significant increase in the plasma membrane localization of ENT1 [73].…”
Section: Pkcs-dependent Regulation Of Drug Transporter Localizationmentioning
confidence: 99%
“…Moreover, recent genetic studies have detected a coordinated expression (colinearity) of OATP1B1 and OATP1B3 in human liver, with respect to mRNA and, to a lesser extent, protein expression . These observations are believed to be linked to posttranscriptional and posttranslational regulation of OATP expression by hepatic nuclear factor 1α (HNF1α) and protein kinase C (PKC), respectively …”
Section: Oatp1b1 Phenotype Information Included As Systems Parametersmentioning
confidence: 99%